Entrepreneurial activity adjacent to small national parks in Southern Finland: Are business opportunities being realised? - Selby, Ashley; Petäjistö, Leena (Finnish Forest Research Institute, 2008)
The study examines the responses of entrepreneurs to the business opportunities created in their locality by national parks by examining the entrepreneurial attitudes of owners of small enterprises, their perceived obstacles to business development and their future development plans, taking into consideration the effects of their local national parks. Two national parks were taken as a basis for the study. The older park, Linnansaari, was initially created in the 1950s and expanded in the 1980s. The younger park, Seitseminen, was created in the 1980s. The business community adjacent to Linnansaari has therefore had twenty years longer to adjust to the presence of a national park in their vicinity. The mean age of enterprises in both surveys was 17 years in the case of Seitseminen and 16 years in the case of Linnansaari. In both surveys, the majority of businesses had been established by their current owners, and around a quarter were developed from previous businesses. The majority of enterprises in both districts operated in more that one segment, but the main line of business accounted for around three-quarters of the firms turnovers. In both surveys, the main lines of business were related to the hospitality segment (accommodation, restaurants and cafés). The average employment created was 1.18 man/years per enterprise in Seitseminen and 1.81 man/years in Linnansaari. In terms of employed people, this was 2.6 employees per enterprise in Seitseminen and 4.8 employees per enterprise in Linnansaari. Entrepreneurs in the Linnansaari survey were more likely to possess a satisficing-attitude to business than entrepreneurs adjacent to Seitseminen. This was also visible in the greater propensity for entrepreneurs in the Seitseminen area to plan new business ventures. Employment growth projections were also more optimistic in Seitseminen. Institutional constraints (including constraints resulting from the local national park) were more commonly perceived by the Seitseminen entrepreneurs, while business environment constraints were more commonly perceived by the Linnansaari entrepreneurs. Operational constraints were also more commonly perceived by the Linnansaari entrepreneurs. An attribute called weak business acumen , in which the entrepreneurs in question perceived a wide range of business constraints, was identified amongst the Linnansaari survey entrepreneurs but not among those in the Seitseminen survey. The national parks in question have only a limited role in local economic development. Their contribution to employment creation and business turnover are modest and will remain so. Few enterprises have been created as a result of the parks, although some business have clearly benefited from the tourism that the parks have created. The national parks are generally considered to be beneficial even though the benefits have not been realised. A greater proportion of entrepreneurs in the Linnansaari survey than in the Seitseminen survey considered their local national park to have a positive or very positive effect on local development in the near future.
Keywords: Etelä-Suomi; kansallispuistot; yrittäjyys; business development; entrepreneurial attitudes; Linnansaari; local enterprise development; national park tourism; opportunity recognition; Seitseminen National Park